Hedonic quality or reward? A study of basic pleasure in homeostasis and decision making of a motivated autonomous robot. (October 2016) - Lewis, Matthew; Cañamero, Lola
We present a robot architecture and experiments to investigate some of the roles that pleasure plays in the decision making (action selection) process of an autonomous robot that must survive in its environment. We have conducted three sets of experiments to assess the effect of different types of pleasure—related versus unrelated to the satisfaction of physiological needs—under different environmental circumstances. Our results indicate that pleasure, including pleasure unrelated to need satisfaction, has value for homeostatic management in terms of improved viability and increased flexibility in adaptive behavior.